The forgotten fifth : African Americans in the age of revolution - Nash, Gary B. (Nathan I. Huggins lectures., 2006)
As the United States gained independence, a full fifth of the country's population was African American. The experiences of these men and women have been largely ignored in the accounts of the colonies' glorious quest for freedom. In this compact volume, Gary B. Nash reorients our understanding of early America, and reveals the perilous choices of the founding fathers that shaped the nation's future. Nash tells of revolutionary fervor arousing a struggle for freedom that spiraled into the largest slave rebellion in American history, as blacks fled servitude to fight for the British, who promised freedom in exchange for military service. The Revolutionary Army never matched the British offer, and most histories of the period have ignored this remarkable story. The conventional wisdom says that abolition was impossible in the fragile new republic. Nash, however, argues that an unusual convergence of factors immediately after the war created a unique opportunity to dismantle slavery. The founding fathers' failure to commit to freedom led to the waning of abolitionism just as it had reached its peak. In the opening decades of the nineteenth century, as Nash demonstrates, their decision enabled the ideology of white supremacy to take root, and with it the beginnings of an irreparable national fissure. The moral failure of the Revolution was paid for in the 1860s with the lives of the 600,000 Americans killed in the Civil War. The Forgotten Fifth is a powerful story of the nation's multiple, and painful, paths to freedom.